2006
DOI: 10.1002/ijc.21907
|View full text |Cite
|
Sign up to set email alerts
|

Sun exposure and host phenotype as predictors of cutaneous melanoma associated with neval remnants or dermal elastosis

Abstract: Recent research suggests that cutaneous melanomas may arise through 2 distinct pathways, characterized by chronic sun exposure on one hand and nevus-prone phenotype of the host on the other. Two histological characteristics of melanoma consistent with these divergent origins are dermal elastosis in adjacent skin and neval remnants contiguous with the tumor, respectively. To further explore causal heterogeneity in melanoma, we compared sun exposure histories and phenotypic characteristics among a population-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
29
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 24 publications
12
29
1
Order By: Relevance
“…The first one is induced by an increased intermittent sun exposure and is associated with a younger age at the time of diagnosis, multiple nevi and CM of the trunk and lower limbs. According to that theory, in our population a higher percentage of CM would be expected to develop on the trunk over the time [2,19]. As in other European countries, tumors were indeed predominantly located on the trunk or lower limb, but there were no statistical changes in the frequency of tumors on the trunk between the periods [5,18].…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The first one is induced by an increased intermittent sun exposure and is associated with a younger age at the time of diagnosis, multiple nevi and CM of the trunk and lower limbs. According to that theory, in our population a higher percentage of CM would be expected to develop on the trunk over the time [2,19]. As in other European countries, tumors were indeed predominantly located on the trunk or lower limb, but there were no statistical changes in the frequency of tumors on the trunk between the periods [5,18].…”
Section: Discussionsupporting
confidence: 49%
“…The second developmental pathway is associated with chronic sun exposure and markers of skin damage (dermal elastosis). CM is located predominantly on the head and neck and occurs later in life [2,19]. On the basis of the increased age of patients at the time of diagnosis (53.32 years in the last observed period vs. 36.58 in the first), it is possible that the increased amount of intermittent sun exposure has led to the changes in tumor development that are usually associated with chronic patterns of exposure [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Patients with cutaneous head and neck melanoma were older than those with melanoma on other skin sites, whereas patients with melanoma on the trunk were younger at diagnosis. 32 A meta-analysis, based on information from 29 published articles and 24 independent study groups, found that associations of intermittent sun exposure, continuous sun exposure, and sunburns were each higher for usually sunexposed anatomic sites than for occasionally sunexposed sites.…”
Section: Discussionmentioning
confidence: 99%
“…The concordant findings from descriptive and analytical studies are consistent with melanomas at different body sites arising through different pathways, but do not shed light on the mechanisms of pathogenesis. To address this issue, investigators have systematically appraised histological features and noted that melanomas arising from a benign melanocytic nevus differ from those arising de novo, being more frequent on the trunk than the head and neck, and being associated with young age and high nevus counts [20][21][22][23]. These congruent findings point to one group of melanomas arising through a high-nevus/low-sunlight pathway (predominantly on the trunk) and another group of mainly head and neck melanomas arising through a low-nevus/high-sunlight pathway.…”
Section: David C Whitemanmentioning
confidence: 99%